A Provenance Study of Early Bronze Age Artefacts Found in Asturias (Spain) by Means of Metal Impurities and Lead, Copper and Antimony Isotopic Compositions. (18th December 2018) - Reguera‐Galan, A.; Barreiro‐Grille, T.; Moldovan, M.; Lobo, L.; de Blas Cortina, M. Á.; García Alonso, J. I.
Abstract : We describe here the first combined isotopic and impurities study on 27 copper artefacts found in the north‐west of Spain. This study follows previous studies on the lead isotopic composition of copper ores in three local mines that were exploited during the Bronze Age. The levels of impurities found were clearly different from ingots and axes, with ingots having much higher levels of impurities. It was not possible to differentiate the origin of the artefacts only by the impurities present. On the other hand, the lead isotopic composition indicated that all artefacts were prepared from local ores, the 'La Profunda' mine being the most probable source for most artefacts that carried out a clear radiogenic lead signature. The copper isotopic composition seemed to be able to differentiate artefacts from the 'El Aramo' mine from those from the 'El Milagro' and 'La Profunda' mines. On the other hand, the antimony isotopic signature was not useful for source allocation.